2004
DOI: 10.1271/bbb.68.1228
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Low-temperature Processing of the Brackish-water Bivalve,Corbicula japonica, on the Ornithine Content of Its Extract

Abstract: The ornithine content of an extract of the brackish-water bivalve, Corbicula japonica, increased when the bivalve was frozen. It was not influenced by the period of freezing. This phenomenon was not apparent in the scallop, little-neck clam, or hard clam. We applied various low-temperature conditions for processing the bivalve from 4 degrees C to -10 degrees C and measured the ornithine content of each extract. The ornithine content was maximized by processing at - 4 degrees C. The increase in this ornithine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…Since ancient times, corbicula, a genus of the clam, has been considered to be good for the liver. They were found to contain 159.9 mg L-ornithine per 100 g of the extract [21], which is high compared with other foods [22] but still a relatively small amount.…”
Section: Introductionmentioning
confidence: 99%
“…Since ancient times, corbicula, a genus of the clam, has been considered to be good for the liver. They were found to contain 159.9 mg L-ornithine per 100 g of the extract [21], which is high compared with other foods [22] but still a relatively small amount.…”
Section: Introductionmentioning
confidence: 99%
“…Brackish-water bivalves, wine, cheese and kimchi are major dietary sources of L-ornithine for humans. 20,21 Ornithine has been proven to be effective in increasing muscle synthesis and rapid metabolization of body fat by stimulating growth hormone secretion, 22,23 improving insulin release, 24 boosting the immune system, 25 enhancing the wound healing response 26 and reducing blood ammonia concentration associated with several hepatic diseases and brain oedema. 27 Many LAB with ornithine-producing ability have been isolated from Korean traditional fermented foods such as kimchi.…”
Section: Introductionmentioning
confidence: 99%
“…indicated that a freshwater clam Corbicula fluminea extract (or referred to as clam essence) con-tained more ornithine than that in a chicken or beef essence in that ornithine is attractive as an ingredient of dietary supplements due to in part that ornithine could promote the secretion of the growth hormone and build muscle (Bucci et al, 1990;Davenport et al, 1990;Uchisawa et al, 2004). This evidence makes brackish-water and freshwater C. fluminea commercially important and has a high market value to Taiwan's aquaculture (http://www.fa.gov.tw).…”
Section: Introductionmentioning
confidence: 99%